Analysis of the Effect of Industrial Sector and Socioeconomic Factors on Environmental Quality of Indonesia (International Journal of Scientific Research and Management (IJSRM), 2024)
https://docs.google.com/document/d/1i_Gkl5eEjA-WSM1aktorzMUTLUmRy8cB/edit